Eficacia de la sal común y extractos de ajos Allium sativum para eliminar monogenoideos branquiales en alevinos de gamitana Colossoma macropomum, Loreto Perú - Vargas de Pina, César Augusto (2022)
The “gamitana” Colossoma macropomum is one of the most important species of the Amazonian ichthyofauna, highly demanded and with significant potential for fish farming and Amazonian development. This species, like others in the Amazon, are affected by parasitic infestations and infections, highlighting infestations by branchial monogenoids, for which, over the years, different chemical products based on various components have been used as treatments. Currently there is a trend for the use of low-cost, easily accessible products that are in harmony with the environment and that also provide good results to combat parasites in farmed fish. Thus, the present work evaluates the efficacy of common salt and garlic extract to reduce the parasitic load of branchial monogenoids present in the “gamitana” C. macropomum. This study was carried out with fish collected from fish ponds at the Fernando Alcántara Bocanegra Research Center (CIFAB) of the Peruvian Amazon Research Institute (IIAP). The gill samples were collected and analyzed in the Parasitology and Aquaculture Health laboratory of the IIAP. The analysis revealed the presence of five species of monogenoids infesting the gills: Anacanthorus spatulatus, Notozothecium janauachaensis, Mymarothecium boegeri and M. iiapensis. To combat these parasites, two products were tested at different concentrations: treatments with salt at a rate of 20, 30 and 40 g/L and treatments with garlic extract at a rate of 20, 25 and 30 ml/L. The results of the study revealed the efficacy of both products, reducing the parasite load in all the treatments used. Within the treatments used, the use of salt at 40g/L and the use of garlic extract at a rate of 30ml/L were the most effective. It is concluded that the doses used can be used in fish farming systems to reduce and/or eradicate parasites by branchial monogenoids in C. macropomum.